Road Surface Assessment of The Kemlagi–Berat Kulon Road Section In Mojokerto District Using The Iri Method - Jadmiko, Fikri; Oetomo, Wateno; Marleno, Risma (Green Publisher Indonesia, 2025)
The Kemlagi–Beratkulon road surface assessment in Mojokerto District covers a section of 3.637 km and features a combination of rigid pavement, flexible pavement, and asphalt. This road plays a critical role as a connecting link between Mojokerto District and Gresik District, supporting transportation and regional connectivity. The primary objective of this study is to evaluate the road surface condition, measure the extent of surface damage, and classify the condition using the International Roughness Index (IRI) method. Data collection was conducted through field surveys with the aid of the Roadroid application, providing real-time measurements of road roughness. The findings reveal that the highest e-IRI value recorded was 1.75 at STA 1+900 to STA 2+000, indicating a road condition classified as